A decision support system to improve planning and management in large irrigation schemes I - Mira da Silva, L.; Park, J.; Keatinge, J.D.H.; Pinto, P. (Elsevier, 2001)
This paper describes a decision support system (DSS) that was developed to improve planning and management for the large irrigation schemes in the Alentejo region of Portugal. The system was designed to help in the analysis and evaluation of the crops and crop systems that can potentially be cultivated, together with identification of limitations affecting crop selection and crop yields. It integrates socio-economic and biophysical data at the field level to analyse the performance of an irrigation scheme in terms of the adoption of irrigation by farmers and farmers’ incomes. The final output is given in the form of specific actions and policies for the irrigated areas. The DSS was designed initially to be used in the Alqueva project, a large irrigation scheme that is under construction in Alentejo. Nevertheless, the final framework is generic in nature, being suitable for planning and policy evaluation in other large irrigation schemes.